Phenotypic Sorting of Pink Salmon Hatchery Strays May Alleviate Adverse Impacts of Reduced Variation in Fitness‐Associated Traits - Julia McMahon; Samuel A. May; Peter S. Rand; Kristen B. Gorman; Megan V. McPhee; Peter A. H. Westley (Ecology and Evolution)
ABSTRACT Maladapted immigrants may reduce wild population productivity and resilience, depending on the degree of fitness mismatch between dispersers and locals. Thus, domesticated individuals escaping into wild populations is a key conservation concern. In Prince William Sound, Alaska, over 700 million pink salmon (Oncorhynchus gorbuscha) are released annually from hatcheries, providing a natural experiment to characterize the mechanisms underlying impacts to wild populations. Using a dataset of > 200,000 pink salmon sampled from 30 populations over 8 years, we detected significant body size and phenological differences between hatchery‐ and wild‐origin spawners, likely driven by competitive differences during maturation and broodstock selection practices. Variation in traits was reduced in hatchery fish, raising biodiversity concerns. However, phenotypic traits of immigrants and locals were positively correlated. We discuss possible mechanisms that may explain this pattern and how it may reduce adverse impacts associated with reduced trait variation. This study suggests that domestication impacts are likely widespread, but local adaptation may be maintained by phenotypic sorting.